1989
DOI: 10.1038/bjc.1989.151
|View full text |Cite
|
Sign up to set email alerts
|

Promotion by ethanol of gastric carcinogenesis induced by N-methyl-N'-nitro-N-nitrosoguanidine in Wistar rats

Abstract: Summary The effects of ethanol (EtOH) on the incidence and histology of gastric cancers induced by Nmethyl-N'-nitro-N-nitrosoguanidine (MNNG) were investigated in Wistar rats. The animals received alternateday i.p. injections of 2.5mlkg-1 body weight of 20% EtOH in 0.9% NaCl solution after 20 weeks of oral treatment with MNNG. Prolonged administration of EtOH resulted in a significant increase in the incidence and number of gastric cancers of the glandular stomach in week 52. However, it had no influence on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Epidemiological studies have implied that alcohol consumption increases the risk of carcinogenesis in smokers (Pitot, 1986;Franco et aL, 1989); and chronic dietary ethanol consumption promotes esophageal and gastric carcinogenesis induced by NMBZA and MNNG separately in experimental animals (Mufti et al, 1989;Iishi et al, 1989), although the effect of ethanol on hepatocarcinogenesis in rats initiated with 3-methyl-4-dimethylaminoazobenzene in the absence of liver injuries has not been observed (Yanagi et at., 1989). We confirmed, first, by the cytogenetic technique in vivo, that alcohol drinking significantly elevated the mean MNF in peripheral-blood lymphocytes from smokers as compared with-that of matched smokers who did not use alcohol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have implied that alcohol consumption increases the risk of carcinogenesis in smokers (Pitot, 1986;Franco et aL, 1989); and chronic dietary ethanol consumption promotes esophageal and gastric carcinogenesis induced by NMBZA and MNNG separately in experimental animals (Mufti et al, 1989;Iishi et al, 1989), although the effect of ethanol on hepatocarcinogenesis in rats initiated with 3-methyl-4-dimethylaminoazobenzene in the absence of liver injuries has not been observed (Yanagi et at., 1989). We confirmed, first, by the cytogenetic technique in vivo, that alcohol drinking significantly elevated the mean MNF in peripheral-blood lymphocytes from smokers as compared with-that of matched smokers who did not use alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that tobacco and alcohol consumption is a strong risk factor for cancer (Franc0 et al, 1989;Yu et al, 1986). Animal experiments have suggested that alcohol could promote chemically induced esophageal and gastric carcinogenesis (Iishi et al, 1989). Some reports indicate that green tea extracts inhibit the mutagenic activity of cigarette-smoke condensate, AFBI and NMBZA, etc.…”
mentioning
confidence: 99%
“…Of note, alcohol further enhanced the NMDA-induced DNA adduct formation in the stomach of the monkeys [ 54 ]. Ethanol also promotes gastric carcinogenesis by stimulating proliferation of the antral epithelial cells [ 55 ]. Thus, prolonged administration of ethanol resulted in a significant increase in the incidence and the number of gastric cancers of the glandular stomach in Wistar rats after N -methyl- N ′-nitro- N -nitrosoguanidine treatment [ 55 ].…”
Section: Mechanisms Underlying Alcohol-induced Gastric and Colonicmentioning
confidence: 99%
“…In addition, when wine or 11% ethanol was coadministered with MNNG in rats, wine or 11% ethanol was found to inhibit the MNNG‐induced gastroduodenal carcinoma 75 . However, an early study reported that the intraperitoneal injection of 20% ethanol in 0.9% sodium chloride increased the incidence and number of the MNNG‐induced gastric cancers of glandular stomach in rats 76 . Because ethanol and sodium chloride were given together, it is difficult to infer that the increased risk was attributable to ethanol or to sodium chloride, which have been shown to increase the incidence of MNNG‐induced gastric tumors in rats 74 …”
mentioning
confidence: 99%